A mathematical model for the simulation of the Magdalena River in the city of Barrancabermeja, Colombia (2021)
The integration of mathematical models allows the simulation of the spatiotemporal behavior of water quality parameters of a river. The representation of reality and different scenarios through simulation makes it possible to know the variations in water quality of a receiving water source associated with liquid discharges. Therefore, for this study, the mathematical model QUAL2K was applied to simulate the water quality of the Magdalena River in the section that crosses the city of Barrancabermeja, Colombia. For this purpose, a database of hydro-climatological records from 1977 to 2020 was used. Among the analyses, dissolved oxygen and biochemical oxygen demand were considered as water quality parameters. As a result of the initial data processing of the distribution tests and Kolmogorov goodness of fit, the best fit with the normal distribution was obtained for the estimation of flow rates. The concentrations of the water quality parameters dissolved oxygen and biochemical oxygen demand were represented in the mathematical model, which shows the dilution capacity of the pollutant loads of the wastewater, due to the high flow of the Magdalena River in the study section.